Теоретическое обоснование экономической эффективности процесса поточных скоростных технологий бурения - Амоша, А.И.; Радченко, В.В.; Зинченко, С.А.; Юшков, Е.А. (Економіка промисловості, 2013)
Статтю присвячено питанням ефективного управління газовиділенням. Проаналізовано вплив швидкості буріння для дегазації на кінцевий результат діяльності шахти. Виведено залежність між розміром капіталу підприємства, мінімально необхідного для буріння, і заданою величиною часу, що витрачається на буріння однієї свердловини.
Ключові слова: управління газовиділенням, дегазація, швидкісні технології буріння. Статья посвящена вопросам эффективного управления газовыделением. Проанализировано влияние скорости бурения для дегазации на конечный результат деятельности шахты. Выведена зависимость между размером капитала предприятия, минимально необходимого для бурения, и заданной величиной времени, затрачиваемого на бурение одной скважины.
Ключевые слова: управление газовыделением, дегазация, скоростные технологии бурения. Dependence between production processes in coal mines causes the influence of the growth rate of coal output on the associated gasemissions. The excess of the marginal rates of the last one leads to increasing costs and endangering lives of workers. This paper focuses on the effective gas emissionmanagement. The purpose of the research is to determine the dependence between the speed of drilling for mine degassing and the final result of mine’s activities and to justify the economic efficiency of these processes. The experience gained in the coal mines shows that investments in the adoption of degassing systems can reduce the downtime, connected with problems of gas emission, improve the safety of production conditions, and create opportunities for utilization of large volumes of gas and emissions reduction. Effective degassing reduces the level of gas explosive risk and risks of accidents. Reduction of these risks in turn leads to the reduction of associated costs.In the paper the influence of speed of drilling for degassing on the final result of mine’s activities is analyzed.The dependence between enterprise’s capital, which is minimally necessary for drilling, and given time spent on the drilling of one well is revealed.This dependence is necessary to determine the value of the company’s capital, providing minimum costs of enterprise connected with the drilling process. The obtained dependences can serve as a basis for buildingsystem dynamic models of the economic process of drilling wellsfor preliminary degassing.
Keywords: gas emissionmanagement, degassing, high-speed drilling technology.